Association of thyroid dysfunction with menstrual irregularities among women attending a tertiary care hospital in western India: a cross-sectional study - Godria, Payal; Tayal, Rijuta; Patel, Chinmay; Jadhav, Srushti; Budhrani, Divyang S.; Ghonia, Meet (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Thyroid dysfunction is a significant yet often underdiagnosed contributor to menstrual irregularities among women of reproductive age. Alterations in thyroid hormone levels can disrupt the hypothalamic-pituitary-ovarian axis, affecting the menstrual cycle in multiple ways. This study aimed to assess the prevalence and patterns of thyroid abnormalities among women presenting with menstrual irregularities in a tertiary care setting in Gujarat, India. Methods: A hospital-based cross-sectional study was conducted at SSG Hospital, Vadodara, from March 2024 to February 2025. A total of 321 women aged 18-45 years presenting with menstrual irregularities were enrolled. Data were collected using a structured questionnaire covering menstrual history, symptoms of thyroid dysfunction, and clinical examination. Thyroid function tests (TSH, FT3, FT4) were conducted for all participants. Statistical analysis was performed using Chi-square and ANOVA to determine associations between menstrual patterns and thyroid function. Results: Out of 321 participants, 99 (30.8%) had thyroid dysfunction. Among them, 65 (65.6%) had subclinical hypothyroidism, 21 (21.2%) had overt hypothyroidism, 9 (9.1%) had subclinical hyperthyroidism, and 4 (4%) had overt hyperthyroidism. Oligomenorrhea (36.3%) and menorrhagia (28.2%) were the most common menstrual disturbances associated with thyroid dysfunction. A significant association was observed between hypothyroidism and menorrhagia (p<0.05), while hyperthyroidism was more frequently linked with hypomenorrhea (p<0.05). Conclusions: Thyroid abnormalities, particularly subclinical and overt hypothyroidism, are common among women with menstrual irregularities. Routine screening for thyroid dysfunction should be integrated into the evaluation of such cases to ensure early diagnosis and intervention.